2017
DOI: 10.4103/1008-682x.172827
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosome microdeletions in nonobstructive azoospermia and severe oligozoospermia

Abstract: The aim of the present work was to present the outcomes of the patients with Y-chromosome microdeletions treated by intracytoplasmic sperm injection (ICSI), either using fresh (TESE) or frozen-thawed (TESE-C) testicular sperm and ejaculated sperm (EJAC). The originality of this work resides in the comparisons between the different types of Y-microdeletions (AZFa, AZFb, and AZFc) and treatments, with detailed demographic, stimulation, embryological, clinical, and newborn (NB) outcomes. Of 125 patients with Y-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…[5]. All patients had a clinical work-up with physical examination, endocrine profile test (follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone) and genetic analysis [6, 7]. Scrotal and transrectal ultrasounds [8] were performed on indication.…”
Section: Methodsmentioning
confidence: 99%
“…[5]. All patients had a clinical work-up with physical examination, endocrine profile test (follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone) and genetic analysis [6, 7]. Scrotal and transrectal ultrasounds [8] were performed on indication.…”
Section: Methodsmentioning
confidence: 99%
“… 26 Reports on the presence of Y chromosome microdeletions in infertile men range from 0.23% to 34.5%, regardless of the number of STSs used, this wide range may be attributed to population/ethnic variances, selection criteria of the patients, methodological aspects, and environmental factors. 27 29 Our results reported AZF-Y chromosome microdeletion in 15.6%, where 4.7% presented in sY245 and 255 together, 1.6% presented in sY84 and 134 together, and 10% (6/60) presented in DAZ1/2 deletion.…”
Section: Discussionmentioning
confidence: 53%
“…AZFa, AZFb or AZFa/b microdeletions are associated with the worst prognosis for sperm retrieval. Although previously sperm retrieval in AZFa and b cases were thought to be deemed to failure [29] , recent studies have reported sperm recovery from a few such cases [30] ; whereas patients with AZFc and AZFb/c microdeletions have a SSR rate of 54.8% and 7.1%, respectively [29] . Moreover, AZFc patients are not necessarily azoospermic, and may be candidates for ICSI using sperm from their ejaculate.…”
Section: Discussionmentioning
confidence: 99%